Tinjauan Awal Naskah Sujarah Penatah (Sejarah Penatah Wayang): Naratif, Kreativitas, dan Legitimasi - Bima Slamet Raharja (Manuskripta, 2023)
The names of wayang puppet makers or penatah (in Javanese) are well known among puppetry aficionados in Indonesia, but little tends to be known about their biographies. It is as if their personalities are overwhelmed by the greatness of their art work. In Yogyakarta’s wayang tradition, a number of names such Resapenatas, Maraguna, Kertiwanda, Prawirasucitra, Prayitnawiguna and Bundhu are very well known. All are considered great wayang makers or artists, with distinct aesthetic styles, but almost all details of their lives are unknown. The only substantial written text to concern penatah is a manuscript titled Sujarah Panatah (A History of Wayang Carvers)written in the early 20th century in Yogyakarta. Tales about carverstake the form of wayang plays. In one play, Ki Mangunwiguna teaches his son how to make a wayang based on prior exemplars. The author of the text tries to connect factual stories and myths about the gods. As in babad stories about kings of yore, wayang makers are presented as if they are also not just ordinary people. This is a means to establish their legitimacy. They are chosen, because they are able to communicate with gods. Alongside the text are wayang-style illustrations, supplementing the creativity of the narrative. This paper will consider the factual basis and validity of stories collected in the Sujarah Penatah, the way the text understands the origins of creativity and its mode for legitimising wayang makers and the continuity of their craft.